The Joint Business Group (KUBE) and Urban Poverty Reduction at Wirobrajan, Yogyakarta City: What and How - Wifata, Erva (FIA UB, 2018)
Drawing on a case study, we examine urban poverty reduction at the level of subdistricts in Indonesia, focus in Wirobrajan subdistrict in Yogyakarta City. This study frames two research questions. Firstly, what is the present status of the implementation of the KUBE program in Wirobrajan, Yogyakarta. Secondly, what are the constraining factors on implementing the KUBE program? Result shows that the implementation of Joint Business Group (KUBE) Program in Wirobrajan Sub-District, Yogyakarta Municipality has not been well implemented. There are six constraint factors to contribute to the failure of the KUBE implementation in reducing the urban povertion in Yogyakarta City. Likewise, Of the 31 groups formed, only 17 active groups remain while 14 other groups are inactive or dispersed. This study suggests that in the selection of business types, they should be in accordance with the skills and abilities of the KUBE member and adjust those needs with the surrounding communityâs needs. Be more selective in choosing group leaders, the individual must have strong leadership ability. Moreover, training should be available for KUBE members and also for Mentors, create proper reward and punishment, increases the number of Mentors and forms teams to monitor and supervise the development of the KUBE programÂ